2016
DOI: 10.1177/1471301216682627
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy in dementia care staff: Experiences from the care home context

Abstract: Perceived self-efficacy is proposed to impact on the psychological health of dementia care staff. The current study adopted a qualitative methodology to increase understanding of the experiences of self-efficacious care assistants. Purposive sampling identified eight care assistants with high levels of self-efficacy. Data from semi-structured interviews were analysed using interpretative phenomenological analysis. Four themes captured experiences of 'feeling torn' between competing demands when providing care;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 17 publications
1
29
0
2
Order By: Relevance
“…In order to understand the person with dementia, the caregivers must be aware of the history, wishes and relations of the individual. Coates and Fossey (2016), Jost et al (2010), and Palmer (2013) described how caregivers attune to personhood in order to fulfil the person's needs: "The caregivers were attuned to the needs, desires, moods and concerns of their family members with dementia; thus, they were attuned to personhood" (Palmer, 2013, p. 224). Working with personhood involved acknowledging the needs and life story of the individual.…”
Section: Taking the Perspective Of The Person With Dementia -The Impomentioning
confidence: 99%
See 2 more Smart Citations
“…In order to understand the person with dementia, the caregivers must be aware of the history, wishes and relations of the individual. Coates and Fossey (2016), Jost et al (2010), and Palmer (2013) described how caregivers attune to personhood in order to fulfil the person's needs: "The caregivers were attuned to the needs, desires, moods and concerns of their family members with dementia; thus, they were attuned to personhood" (Palmer, 2013, p. 224). Working with personhood involved acknowledging the needs and life story of the individual.…”
Section: Taking the Perspective Of The Person With Dementia -The Impomentioning
confidence: 99%
“…According to Coates and Fossey (2016), Palmer (2013), and R. Ward et al (2008), attunement requires the caregivers' emotional involvement when they interact with the person. Care work was described as deeply emotional work, and to understand and attune to the person, emotional openness and awareness was central (Coates & Fossey, 2016). "Seemingly valuing the emotional content in the relation with the residents as a prerequisite for understanding them" (Häggström et al, 1998, p. 254).…”
Section: Developing Mutual Understanding Through An Empathic Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these problems mentioned above are important because they decrease workers' health and retention, their job satisfaction and the quality of care (Ravenswood, Douglas, & Haar, 2018;George, Hale, & Angelo, 2017;Zhang, Punnett, & Nannini, 2017;Estabrooks et al, 2015). For these reasons, it is necessary to create educational programs and interventions on reducing dysfunctional coping strategies, learning healthy sleep practices, increasing self-efficacy (Coates & Fossey, 2019) and improving communication (George et al, 2017). Islam, Baker, Huxley, Russell, & Dennis (2017) highlight the importance of dementia training in care homes, in order to reduce stress in professionals, especially in nursing and larger care homes.…”
Section: Training Programs For Caregiversmentioning
confidence: 99%
“…A qualitative study by Coates found increased dilemma among care workers in the process of caregiving due to the lack of con dence in their role [10]. A study in Canadian long-term care home found a high level of perceived self-e cacy to provide palliative care among the care workers though there was a knowledge gap on palliative care [11].…”
Section: Introductionmentioning
confidence: 99%